Hydration or dehydration: competing effects of upper tropospheric cloud radiation on the TTL water vapor - L. Wu (Atmospheric Chemistry and Physics, 2012)
A tropical channel version of the Weather Research and Forecasting (WRF) model is used to investigate the radiative impacts of upper tropospheric clouds on water vapor in the tropical tropopause layer (TTL). The WRF simulations of cloud radiative effects and water vapor in the upper troposphere and lower stratosphere show reasonable agreement with observations, including approximate reproduction of the water vapor "tape recorder" signal. By turning on and off the upper tropospheric cloud radiative effect (UTCRE) above 200 hPa, we find that UTCRE induces a warming of 0.76 K and a moistening of 9% in the upper troposphere at 215 hPa. However, UTCRE cools and dehydrates the TTL, with a cooling of 0.82 K and a dehydration of 16% at 100 hPa. The enhanced vertical ascent due to UTCRE contributes substantially to mass transport and the dehydration in the TTL. The hydration due to the enhanced vertical transport is counteracted by the dehydration from adiabatic cooling associated with the enhanced vertical motion. UTCRE also substantially changes the horizontal winds in the TTL, resulting in shifts of the strongest dehydration away from the lowest temperature anomalies in the TTL. UTCRE increases in-situ cloud formation in the TTL. A seasonal variation is shown in the simulated UTCRE, with stronger impact in the moist phase from June to November than in the dry phase from December to May.